PENERAPAN MODEL PEMBELAJARAN KOOEPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Samsur (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the lack of IPS student learning outcomes can be seen from the results of the students' social studies class V SD Negeri 54 Sebangar with an average value of 60.65. Therefore, the researchers provide an alternative implementation strategies in the classroom to the application of learning models kooeperatif make a match type in the class V SD Negeri 54 Sebangar in the academic year 2014/2015. This research aims to improve learning outcomes IPS V grade students of SD Negeri 54 Sebangar with the application of learning models kooeperatif make a match type in the class V Implementation Strategy. Form of research is the Classroom Action Research (PTK) with 2 cycles. Based on research data anlisis after applying of learning models kooeperatif make a match type, the average percentage of the activity of teachers in the first cycle 74.99% increased to 91.06% in the second cycle. The average percentage of student activity also increased, namely 67.85% in the first cycle increased to 82.14% in the second cycle. Student learning outcomes in basic score by the average value of 60.65 and the first cycle increased with an average value of 75.00 class with a 23.66% increase in the percentage of learning outcomes and the percentage of students who completed 84.61%, and the second cycle increased again by an average of 82.30 with the percentage improvement classlearning outcomes 35.69% and the percentage of students who completed 88.46%. These results indicate that the application the application of learning models kooeperatif make a match type in the class V IPS grade students of SD Negeri 54 Sebangar.